2000
DOI: 10.1007/s100870050027
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Efficiency of Rainfed and Irrigated Bread Wheat in a Mediterranean Environment

Abstract: Supplemental irrigation (SI) is defined as the application of a limited amount of water to rainfed crops when In West Asia and North Africa, shortage of water limits wheat precipitation fails to provide the essential moisture for (Triticum aestivum L.) production. Current irrigation practices aim at maximizing grain yield, but achieve lower return for the water normal plant growth. This practice has shown potential consumed. Maximizing water use efficiency (WUE) may be more in alleviating the adverse effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
56
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 4 publications
16
56
0
2
Order By: Relevance
“…The highest WP I , 2.15 kg m -3 , was achieved under deficit irrigation (W1) and N2 strategies in 2002-03, indicating that the irrigation water and nitrogen were most efficiency used in this treatment. Similar results were reported by earlier researchers working with deficit irrigation of wheat and other crops (Oweis et al, 2000;Zhang et al, 2004;Ali et al 2007). The lowest WP I , 0.79 kg m -3 , was obtained under the greatest irrigation amount (W4) and lowest N1 strategy in 2007-08.…”
Section: Water Productivity Indicessupporting
confidence: 91%
“…The highest WP I , 2.15 kg m -3 , was achieved under deficit irrigation (W1) and N2 strategies in 2002-03, indicating that the irrigation water and nitrogen were most efficiency used in this treatment. Similar results were reported by earlier researchers working with deficit irrigation of wheat and other crops (Oweis et al, 2000;Zhang et al, 2004;Ali et al 2007). The lowest WP I , 0.79 kg m -3 , was obtained under the greatest irrigation amount (W4) and lowest N1 strategy in 2007-08.…”
Section: Water Productivity Indicessupporting
confidence: 91%
“…; Figure 12) appeared consistent with values derived from previous experiments on wheat crops, both in Mediterranean and in temperate climates [87,88]. Water use efficiency experienced a high variability, which is mainly explained by sowing practices: the determination coefficient between the day of plant emergence and the water use efficiency is 0.59.…”
Section: Crop Production Seasonal Evapotranspiration and Water Use Esupporting
confidence: 88%
“…The goal of supplemental irrigation is not to maximise yield per unit area but to optimise water productivity (benefit per unit water). Results of research experiments have shown substantial increases in crop yields and water productivity in response to the application of relatively small amounts of supplemental irrigation (Ghahraman and Spaskhah, 1997;Oweis et al, 1998Oweis et al, , 2000Fox and Rockström, 2003;Tavakoli and Oweis, 2004;Oweis and Hachum, 2006). At the farm level, supplemental irrigation increases yields, water productivity, and stability of crop production under different climatic conditions.…”
Section: Introductionmentioning
confidence: 99%